Growth in the High‐Risk Newborn Infant Post‐Discharge: Results from a Neonatal Intensive Care Unit Nutrition Follow‐up Clinic. (21st February 2020) - Zhang, Xiaoyi; Donnelly, Brynn; Thomas, Jessina; Sams, Lauren; O'Brien, Karen; Taylor, Sarah N.; Jump, Candi S.
Abstract: Growth and nutrition in preterm infants have long‐term implications for neurodevelopmental and cardiometabolic outcomes. Many infants are discharged from the neonatal intensive care unit (NICU) with growth restriction, but often without a specialized team to monitor postdischarge growth. At our institution, we addressed our ongoing concerns for the health and growth of these infants post‐discharge by creating a Nutrition NICU Graduate Clinic. This clinic serves infants discharged from our NICU who were born with very low birth weight, had difficulty growing or feeding while inpatient, had a gastrostomy tube placed during hospitalization, or were deemed high risk for other reasons by our neonatal team, with the first clinic visit within 5 weeks of discharge. Data from our first 227 patients at time of discharge, first clinic visit, and any available second clinic visits are described. Anthropometrics show a high rate of extrauterine growth restriction at time of discharge with continued growth restriction at follow‐up. Feeding regimens prescribed at discharge and variations from the prescribed regimen at time of follow‐up are described. At time of first clinic visit, most patients (92.2%) required a medical or dietary intervention by our team. Our findings illustrate the need for early and specialized nutrition follow‐up in this patient population to improve growth trajectory post‐discharge.